Carbon-based low-pressure filtration membrane for the dynamic disruption of bacteria from contaminated water. (1st April 2022) - Anand, Anisha; Unnikrishnan, Binesh; Mao, Ju-Yi; Lin, Chin-Jung; Lai, Jui-Yang; Huang, Chih-Ching
Highlights: Fabrication of graphene oxide/carbonized nanogels (GO@CNGs) hybrid membranes. Macroporous carbon nanocomposite-based membranes could eliminate > 99% bacteria. GO@CNGs membrane causes dynamic disruption of bacterial membranes upon passing through it. Gravity driven GO@CNGs filtration provides a sustainable water purification. Abstract: Carbon-based materials, especially graphene oxide (GO) and carbon dots possessing antibacterial properties, are widely used for various applications. Recently, we reported the antibacterial and antioxidant properties of carbonized nanogels (CNGs) for the treatment of bacterial keratitis, and as a virostatic agent against infectious bronchitis virus. In this work, we demonstrate the use of CNGs/GO nanocomposite (GO@CNGs) membrane for the efficient removal of Gram-negative ( E. coli ) and Gram-positive ( S. aureus ) bacteria from contaminated water. The GO@CNGs composite membrane with an optimized ratio of GO to CNGs could achieve more than 99% removal efficiency toward E. coli and S. aureus . Various strains of bacteria interact differently with the membrane, and hence the membrane shows different removal rate, which can be optimized by controlling the interaction time through regulating the water flux. The GO@CNGs membrane with an active area of 2.83 cm 2 achieved > 99% bacterial removal efficiency at a water flux of 400 mL min –1 m –2 . The dynamic disruption of bacteria by GO@CNGs plays a crucial role in eliminating the bacteria. Rather than filtering out the bacteria, GO@CNGs membrane allows them to pass through it, interact with the bacteria and rupture the bacterial cell membranes. Our GO@CNGs membrane shows great potential as a filter to remove bacteria from contaminated water samples, operating under tap water pressure without any extra power consumption. Graphical abstract: Image, graphical abstract